Aspirations and women's empowerment: Evidence from Kyrgyzstan - Kosec, Katrina; Akramov, Kamiljon T.; Mirkasimov, Bakhrom; Song, Jie; Zhao, Hongdi (Wiley, 2022)
There is an enormous interest in development interventions aimed at reducing behavioural poverty traps, including by raising women's and girls' aspirations, or future-oriented goals. However, little is known about how women's aspirations influence their gender attitudes, the marriages into which they select and their involvement in intra-household decision-making. We find that women in Kyrgyzstan with higher aspirations are more likely to espouse egalitarian gender attitudes, as are their husbands, and their husbands have higher aspirations. They also live in households in which women play a greater role in decision-making, and in which spouses are more likely to agree about women's roles in decision-making.